Quantitative Structure Activity Relationships Studies on Benzimidazole Derivatives as antibacterial agents against Escherichia coli - Sachan, Shailja; Mishra, Aradhana; Tiwari, Santosh; Tiwari, Santosh Kumar; Pandey, Vikash (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
In a continuing effort to develop novel Benzimidazole endowed with better pharmacological profiles. A series of Benzimidazole derivatives were designed on the basis of previously developed QSARs. These drugs offer novel mechanisms of action and expanded spectrums of activity over traditional treatment option. However, with these new agents comes the need for increased awareness of the potential interactions and toxicities associated with these drugs. The best models for different antibacterial agents against Escherichia coli were first validated by leave-one-out cross validation procedure. It was revealed that topological, physicochemical and indicator parameters were found to have overall significant correlationship with antibacterial activity against Escherichia coli and these studies provide an insight to design new molecules.